Propagación vegetativa aplicando hormonas de crecimiento en ramillas de café (Coffea arábica) en las cuatro fases lunares en el cantón Puerto Quito - Orta Yangua, Edy Orlando (2015)
This research was conducted in the Campus Brisas del Rio Chad km 127 Canton Puerto Quito province of Pichincha Ecuador, under the geographical coordinates 77 º 32 '9.7 "west elevation, 1 09` 25.1 "altitude sur The experiment lasted 120 days. A complete randomized design was used. four new, waxing, full and waning moon phases were studied. The lowest survival rate was shown by treatment of the new moon with an average of 13.6. The highest mortality rate was shown by treatment of the full moon with an average of 0.07.El treatment had the highest number of shoots was the waning moon with an average of 1.80. The more leaves had the treatement of the waning moon with an average of 7.48 leaves Most outbreaks height record what treatment waning moon with an average of 9.56 cm. The variable root as many present as treating waning moon with an average of 3.64 roots. Most root length had the treatement crescent with an average of 19.40 cost as much benefit in the waning moon, because for every dollar invested a return of 0.25 cents, followed by the crescent moon that for every dollar invested a profit of 0.18 cents is obtained in other treatments is obtained no benefits were obtained.